The relative importance of motivation in the school context - Reschke, Katharina (2020)
A high degree of motivation is an important prerequisite for learning and school achievement (Spinath, 2010). The purpose of this dissertation was to expand the knowledge about the importance of motivation in the context of school, both relative to other well-established predictors and as a potential mediating and explaining factor. The goal was to examine different aspects of the predictive power of motivation for school achievement and teachers’ judgment of students’ aptitude. In particular, this dissertation aimed at examining the interplay between motivation and other student characteristics, such as intelligence and socio-economic status (SES), when predicting school achievement. Study 1 is a meta-analysis that systematically examined the relative importance of both motivation and intelligence for school achievement. This meta- analysis summarized 74 primary studies (N = 80,145) that reported correlations between motivation, intelligence, and school achievement. First, significant positive average correlations between motivation and school achievement (r = .27), between intelligence and school achievement (r = .44), and between intelligence and motivation (r = .17) were found. Moderator analyses showed no differences in these correlations depended on the achievement measures used such as school grades or standardized test achievement. The association between motivation and school achievement was higher for expectancies as a motivational construct compared to values. The correlation between intelligence and school achievement was higher for general intelligence than for nonverbal intelligence. No moderator effects were found for grade level, school type, gender, or continent. Second, a meta-analytic path model showed that both intelligence and motivation were important predictors of school achievement and explained 24% of its overall variance. Of this 24%, intelligence alone accounted for 66%, whereas motivation alone accounted for 16%. Motivation and intelligence together accounted for 16%. Even though intelligence was a stronger predictor of school achievement, motivation incrementally predicted school achievement over intelligence. Therefore, both intelligence and motivation are student characteristics that should be considered when predicting school achievement. Study 2 focused on the underlying effects of the relationship between parents’ SES and students’ school achievement. Students’ motivation and intelligence were examined as mediators of this relationship. Longitudinal data from the Programme for International Student Assessment (PISA) were analyzed (two measurement occasions). The sample consisted of N = 6,020 German students (MAge = 15.5 years, SD = .55) who were in 9th grade at the time of the first (2003) and in 10th grade at the time of the second measurement occasion (2004). Students completed a questionnaire on their SES, math-specific self-concept, self-efficacy, and interest in math. Moreover, students’ intelligence and mathematical competence were assessed. The results showed a small to moderate significant positive correlation between parents’ SES and students’ test achievement in math. Motivation partially mediated the relationship between parents’ SES and students’ achievement. This mediating effect remained significant after including students’ intelligence and prior test achievement as additional mediators. These findings are important to understand the underlying mechanisms of the association between SES and school achievement. They are also relevant for discussing topics such as educational equality. Study 3 investigated potential reciprocal effects between students’ motivation, their school achievement in form of grades, and teachers’ judgments of students’ aptitude. It was hypothesized that teachers’ judgments of students’ aptitude are predicted by students’ motivation and their school grades. Also, it was expected that teachers’ judgments of students’ aptitude determine students’ grades and motivation. A sample of N = 519 students in elementary school gave self-reports on their math- specific motivation in form of academic self-concepts and intrinsic task values in math. Teachers (N = 27) evaluated students’ aptitude in math and gave information about students’ grades in math. Measurements were performed four times from the end of 3rd grade until the end of 4th grade. Cross-lagged panel models showed that teachers’ prior judgments of students’ aptitude had significant positive effects on students’ grades in math but not on their motivation. Students’ prior math grades and their academic self-concepts significantly predicted teachers’ subsequent judgments of students’ aptitude. These findings are very important for understanding which factors play a role in teachers’ judgments of students’ aptitude. Important practical implications will be discussed later. To summarize, the findings of all studies showed that motivation plays an important role in the school context, both relative to other well-established predictors and as a potential mediating and explaining factor. In Study 1, motivation predicted school achievement over and beyond intelligence. In Study 2, motivation mediated the relationship between parents’ SES and students’ school achievement. In Study 3, motivation in form of students’ academic self-concepts longitudinally predicted teachers’ judgments of students’ aptitude. The findings of this dissertation have a number of implications for theory and future research but can also give practical advice for school contexts.
Keywords: Hochschulschrift